Applications of Lignin‐Dervied Carbon Quantum Dots: Current Status and Challenges - Xiuxin Yin; Zhili Zhang; Fengfeng Li; Maoqing Fu; Tianci Qin; Xingxiang Ji; Yuanyuan Wang; Zhiwen Wang; Shaolong Sun (Exploration)
ABSTRACT In recent years, lignin has attracted substantial attention from researchers because of its diverse sources, low cost, and renewability. The effective functionalization and enhanced value‐added utilization of lignin have successfully addressed the challenges associated with biomass resource waste, low utilization rate, high material cost, and underwhelming performance in energy, environmental protection, and medical applications. The emergence of lignin carbon quantum dots (LCQDs) has opened new avenues for the development and utilization of lignin by offering exciting opportunities for their applications. LCQDs possess unique characteristics such as fluorescence properties, size effect, surface effect, and interface effects, which are promising for applications in many fields. This paper provides a comprehensive overview of the structure and applications of lignin with a specific focus on the preparation method of LCQDs as well as their various applications in drug delivery systems, electrode material fabrication, and antibacterial agent development. Furthermore, this study offers valuable insights into the prospects of LCQDs and aims to contribute to their functional development. Finally, the challenges associated with leveraging the fluorescence properties of LCQDs are discussed, along with potential directions for future research.